2005
DOI: 10.1055/s-2005-837745
|View full text |Cite
|
Sign up to set email alerts
|

In VivoAntimalarial Activity of Essential Oils fromCymbopogon citratusandOcimum gratissimumon Mice Infected withPlasmodium berghei

Abstract: The essential oils obtained by hydrodistillation from fresh leaves of Cymbopogon citratus and Ocimum gratissimum growing in Cameroon were analyzed by GC and GC/MS. The main constituents of the oil of Ocimum gratissimum were gamma-terpinene (21.9 %), beta-phellandrene (21.1 %), limonene (11.4 %) and thymol (11.2 %), while the oil of Cymbopogon citratus contained geranial (32.8 %), neral (29.0 %), myrcene (16.2 %) and beta-pinene (10.5 %). The effects of these oils on the growth of Plasmodium berghei were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 11 publications
3
72
1
7
Order By: Relevance
“…& Thonn. (Euphorbiaceae) (Adjobimey et al, 2004), Euphorbia hirta Linn (Euphorbiaceae) (Tona et al, 1999;Liu et al, 2007) and Ocimum gratissimum L. Labiatae (Tchoumbougnang et al, 2005). In contrast, some of the plants evaluated in this study have previously been reported to lack antiplasmodial activity, but activity was detected in this study.…”
Section: Resultscontrasting
confidence: 53%
“…& Thonn. (Euphorbiaceae) (Adjobimey et al, 2004), Euphorbia hirta Linn (Euphorbiaceae) (Tona et al, 1999;Liu et al, 2007) and Ocimum gratissimum L. Labiatae (Tchoumbougnang et al, 2005). In contrast, some of the plants evaluated in this study have previously been reported to lack antiplasmodial activity, but activity was detected in this study.…”
Section: Resultscontrasting
confidence: 53%
“…When acting on yeast, they were found to inhibit mitochondrial respiration, the proton pump activity and K+ transport, and to increase membrane fluidity [69]. They also exhibit pest-destroying properties against the protozoon Plasmodium berghei (malaria vector [70]), insecticidal properties against lice [71] and the mosquito Aedes aegypti [51] as well as an antiseptic effect on oral bacterial flora [50]. In general, they exert a considerable antibacterial effect, especially on a methicilline-resistant S. aureus and other Gram-positive and Gram-negative bacteria [43].…”
Section: Beta-pinenesmentioning
confidence: 99%
“…Además, los aceites esenciales de Achillea millefolium L (milenrama), Syzygium aromaticum L (clavo) y Ocimun basilicum L (albahaca) también han demostrado su actividad inhibitoria del desarrollo de epimastigotes y tripomastigotes de T. cruzi (30) . Es probable que la actividad tripanocida de los aceites esenciales de Cimbopogon citratus y Aloysia triphylla se encuentre relacionada con su componente principal: el citral (una mezcla de geranial y neral), dado que esta es una reconocida sustancia con propiedades antibacterianas y antiparasitarias (antimalárica) (31) .…”
Section: Discussionunclassified